Comparison of pulmonary function test results before and after exercise in junior high school students - Hendy Zulkarnain; Munar Lubis; Gabriel P.; Ridwan M. D.; Helmi M. Lubis (Indonesian Pediatric Society Publishing House, 2010)
Background During exercise, bronchoconstriction occurs due to heat loss from mucosal respiratory ract. Exercise test can be performed to evaluate hyper-reactivity of the bronchus. The examination of pulmonary function is beneficial to confinn the diagnosis, to determine precipitating factors, and to evaluate disease severity and therapeutic response. Objective To compare pulmonary function test values before and after exercise in junior high school students aged 13 to 15 years. Methods Experimental study of 60 junior high school students from Bilah Hulu was performed using spirometry to evaluate pulmonary function before and after eight minutes of exercise.  Results Functional vital capacity (FVC) values before and after eight􀁅minute exercise were 2.20 (SD 0.52) and 2.18 (SD 0.42), respectively. There was no significant difference between FVC values before and after exercise (P>0.05). The mean forced expiratory volume in 1 second (FEV 1) values before and after eight minutes of exercise were 2.21 (SD 0.42) and 2.13 (SD 0.50) respectively. There was no significant difference between FEV 1 before and after the exercise (P>0.05). Conclusion Eight􀁅minute exercise does not influence the pulmonary function test results in healthy children.